THE INFLUENCE OF CAREER DEVELOPMENT, WORK MOTIVATION, AND COMPETENCE ON EMPLOYEE PERFORMANCE - Eko Santoso; Tri Dewi Untari (Universitas Tulungagung, 2024)
This study analyzes the influence of career development, work motivation, and competence on employee performance on CVs. Dimas Tulungagung and to determine the variables that have a dominant influence on employee performance at CV. Dimas Tulungagung. The usefulness of this study is that it can be used as a suggestion for CV. Dimas Tulungagung to determine the phase related to Human Resources. This is expected to contribute to decision-making related to Human Resources. This research is explanatory; the number of samples in this study is 70 employees. The regression analysis results show that career development, work motivation, and competence simultaneously significantly affect employee performance at CV. Dimas Tulungagung and the study's results show that competence dominates employee performance at CV. Dimas Tulungagung.